Pelatihan Pengolahan Sampah Rumah Tangga menjadi Produk Bernilai Ekonomis bagi Masyarakat Perkotaan (Kecamatan Baguala Kota Ambon) - Teddy Ch Leasiwal; Bin Raudha A.Hanoebun; Rukmuin Wilda Payapo; Amin Ramly; Fredy H. Louhenapessy (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Household waste management in urban areas is a complex environmental challenge due to the increasing volume of waste each year. Poorly managed waste has the potential to cause environmental issues, such as water, soil, and air pollution, as well as health impacts on the community. This Community Service Program (PKM) aims to provide training in processing household waste into economically valuable products for urban communities in Baguala District, Ambon City. The training activities encompass various stages, from education on waste sorting, techniques for processing organic waste into compost, to processing inorganic waste into crafts and recycled products with market value. Through this training, it is hoped that the community will understand the importance of sustainable waste management and be able to utilize household waste as an additional source of income. The results of the activities show that participants are able to process household waste into economically valuable products, such as compost and recycled crafts. This program not only contributes to reducing urban waste but also supports community economic empowerment through a circular economy approach.